Complications of voice prostheses and their management in patients after laryngectomy - Bała, Kamila; Staszko , Natalia (Quality in Sport, 2025)
Total laryngectomy remains the treatment of choice for advanced stages of laryngeal cancer. Voice prostheses are considered by many authors to be the gold standard for restoring speech after total laryngectomy. Their effectiveness has led to their widespread adoption in clinical practice. As a result, the population of patients using such devices is steadily increasing, which is reflected in a growing scientific interest in this area. This trend has generated an expanding number of studies focused on the analysis of potential complications, available treatment methods in this group of patients. The aim of this review is to analyze potential complications and their management options in patients with tracheoesophageal voice prostheses. All authors independently searched the PubMed database using the following keywords: “tracheoesophageal voice prosthesis,” “primary tracheoesophageal puncture,” “tracheoesophageal fistula,” “laryngectomy,” and “voice prosthesis complications.” Particular attention was paid to reflux therapy with proton pump inhibitors and the potential benefits for patients after laryngectomy. Another important issue discussed in the article concerns methods aimed at reducing biofilm formation on voice prostheses, which consequently translates into longer device lifespan. The effectiveness of botulinum toxin type A was compared with surgical treatment in patients with impaired voice due to spasm of the middle and inferior pharyngeal constrictor muscles (PCM). The studies discussed in this article contribute to improving the quality of life of patients with voice prostheses after laryngectomy. Nevertheless, further research is needed to determine the safety and long-term outcomes of the methods used to manage complications.